PENGARUH METODE PEMBELAJARAN DAN MOTIVASI BELAJAR TERHADAP KESULITAN MAHASISWA DALAM MEMAHAMI MATERI MATA KULIAH BAHASA INGGRIS (STUDI PADA KAMPUS ITBKPP JURUSAN S1 KEWIRAUSAHAAN) - Susiati, Susiati _; Adhitia, Pius (DINAMIS, 2024)
The background of this study is about the condition of students in the campus ITBKPP who are not get the good result in learning English. The method which is used in this study is quantitative. The aim of this study is about the influence of learning method and motivation of students for the difficulty to understand the materials of English lecture. This study explores the influence of teaching methods and learning motivation on students' difficulties in understanding the material of English language courses. The research employs a quantitative approach. The analysis results show that teaching methods (t = 1.868) and learning motivation (t = 1.858) significantly affect students' abilities, with significance values of 0.04 and 0.00, respectively. Effective teaching methods and high motivation can reduce the learning difficulties faced by students. The F-test indicates a significant interaction between these two independent variables (F = 3.80) concerning the dependent variable. These findings underscore the importance of evaluating and adjusting teaching strategies, as well as enhancing motivation, to improve students' understanding. In the educational context, the results highlight the need for developing interactive teaching methods and creating supportive learning environments to mitigate students' learning difficulties.